Glycoengineering of Therapeutic Antibodies Enhances Monocyte/Macrophage-Mediated Phagocytosis and Cytotoxicity - Herter, Sylvia (AAI, 2014)
Therapeutic Abs possess several clinically relevant mechanisms of action including perturbation of tumor cell signaling, activation of complement-dependent cytotoxicity, Ab-dependent cellular cytotoxicity (ADCC), Ab-dependent cellular phagocytosis (ADCP), and induction of adaptive immunity. In view of the important role of phagocytic lineage cells in the mechanism of action of therapeutic Abs, we analyzed FcγR receptor-dependent effector functions of monocytes and macrophages triggered by glycoengineered (GE) Abs (having enhanced FcγRIIIa [CD16a] binding affinity) versus their wild-type (WT) counterparts under different experimental conditions. We first defined the precise FcγR repertoire on classical and nonclassical intermediate monocytes—M1 and M2c macrophage populations. We further show that WT and GE Abs display comparable binding and induce similar effector functions (ADCC and ADCP) in the absence of nonspecific, endogenous IgGs. However, in the presence of these IgGs (i.e., in a situation that more closely mimics physiologic conditions), GE Abs display significantly superior binding and promote stronger monocyte and macrophage activity. These data show that in addition to enhancing CD16a-dependent NK cell cytotoxicity, glycoengineering also enhances monocyte and macrophage phagocytic and cytotoxic activities through enhanced binding to CD16a under conditions that more closely resemble the physiologic setting.